More than meets the eye: Orbital swelling in an adolescent with sickle cell disease - Rachel Elizabeth Hicks; Mohammed Alsabri; Mario Peichev; Viswanathan Kusum (International Journal of Hematology-Oncology and Stem Cell Research, 2023)
Periorbital swelling is a clinical presentation with a broad differential and potentially deleterious consequences. Causes range from benign, including allergic reaction, to vision- and life-threatening, including orbital cellulitis and orbital infarction. The recent climate of SARS-CoV-2 has further complicated this differential, as the virus poses broad clinical presentations with new manifestations reported frequently. Rapid identification of the underlying etiology is crucial, as treatment approaches diverge greatly. Here, we report the case of an African American adolescent male with a history of homozygous sickle cell anemia presenting to an inner city hospital with bilateral periorbital swelling amid the coronavirus pandemic. Differentials including orbital cellulitis, COVID-MIS-C, orbital inflammatory syndrome, Hoagland sign, and orbital infarction secondary to sickle cell crisis are contrasted. We contrast our case with 12 case reports of orbital infarction in the setting of sickle cell crisis within the past 10 years, highlighting how these presentations, along with commonly reported findings of orbital infarction, compare with our patient.